PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN MINAT BELAJAR DAN HASIL BELAJAR DALAM PEMBELAJARAN IPA SD - rini siswanti (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
AbstackA common problem related to this research is the application of discovery learning learning model to improve the critical thinking ability and learning outcomes of the elementary school class. The Government implements that in the curriculum of 2013 students are required to think critically that can improve student learning outcomes. Learning discovery learning model is a learning model that improves on kontruktivisme, about the importance of the learning process involving students and teachers can be active in the learning process. This study aims to find out how the process of learning in the classroom to improve the ability of critical thinking and student learning outcomes by menggunkan model of learning discovery leraning in class V. The research used is research using document study with data collection result of previous research result. In pengemabilan learning methods discovery leraning teachers and students can improve the ability of critical thinking and learning outcomes.